HUMAN RESOURCE MANAGEMENT STRATEGY IN IMPROVING TEACHER PROFESSIONALISM IN PESANTREN - Arrifa’i, Ahmad; Risnita; Sodiah (re-JIEM (Research Journal of Islamic Education Management), 2025)
This study examines human resource management (HRM) in enhancing teacher professionalism at Pondok Pesantren Almunawwaroh Tahfiz Walhadist Sungai Misang. Employing a descriptive qualitative approach, the research reveals that teacher professionalism encompasses not only pedagogical competence but also moral integrity, scholarly commitment, and multifaceted roles as educators, spiritual mentors, and community leaders. The pesantren’s HRM system integrates Islamic values into planning, morally grounded recruitment, continuous training, multi-source performance evaluation, and genuine support for teacher well-being, despite financial constraints. Enabling factors include visionary leadership, a spiritually rooted learning culture, and institutional commitment to professional development. Key challenges involve limited funding, traditional management practices, and insufficient external collaboration. The pesantren’s success in producing graduates who excel academically while demonstrating spiritual maturity underscores how HRM aligned with Islamic principles; such as tazkiyah (self-purification), ikhlas (sincerity), and tawakkul (trust in God) can foster holistic education. These insights offer valuable lessons for both religious and mainstream educational institutions on harmonising professional standards with ethical and spiritual foundations